Students’ experiences of blended learning in Accounting Education at the Durban University of Technology - Hiralaal, Anita (South African Journal of Higher Education, 2016)
The Durban University of Technology guided by the Higher Education Qualifications Framework (HEQC) identified e-learning as one of their objectives in the curriculum renewal process. To explore the impact of e-learning, blended learning, a combination of online and face-to-face interaction was implemented as a teaching approach in Accounting Education. This paper explores Accounting Education students’ experiences of blended learning The study was conducted using an action research methodology. Data was collected from the 2011 fourth year cohort of Accounting Education students who were exposed to blended learning for a period of 18 months. This data was gathered and analysed to determine students’ perceptions of a blended learning approach in Accounting Education. Results indicated that students experienced significant improvements in their performance in Accounting Education, they were more motivated to learn, they experienced increased levels of independence in the learning process and they had acquired a deeper understanding of the subject matter. Results also showed that additional learning materials were readily available via hyperlinks to websites, the students got immediate feedback from online assessments, there was greater lecturer-student interaction as well as student-student interaction through meaningful dialogue with peers and finally there was increased convenience, flexibility and access to learning in the blended learning environment. Key words: Curriculum renewal, blended learning, on-line classroom, action research, accounting education